Novel Iron Oxide Nanoparticles Induce Ferroptosis in a Panel of Cancer Cell Lines - Roberto Fernández-Acosta; Claudia Iriarte-Mesa; Daniel Alvarez-Alminaque; Behrouz Hassannia; Bartosz Wiernicki; Alicia M. Díaz-García; Peter Vandenabeele; Tom Vanden Berghe; Gilberto L. Pardo Andreu (Molecules, 2022)
The use of nanomaterials rationally engineered to treat cancer is a burgeoning field that has reported great medical achievements. Iron-based polymeric nano-formulations with precisely tuned physicochemical properties are an expanding and versatile therapeutic strategy for tumor treatment. Recently, a peculiar type of regulated necrosis named ferroptosis has gained increased attention as a target for cancer therapy. Here, we show for the first time that novel iron oxide nanoparticles coated with gallic acid and polyacrylic acid (IONP–GA/PAA) possess intrinsic cytotoxic activity on various cancer cell lines. Indeed, IONP–GA/PAA treatment efficiently induces ferroptosis in glioblastoma, neuroblastoma, and fibrosarcoma cells. IONP–GA/PAA-induced ferroptosis was blocked by the canonical ferroptosis inhibitors, including deferoxamine and ciclopirox olamine (iron chelators), and ferrostatin-1, the lipophilic radical trap. These ferroptosis inhibitors also prevented the lipid hydroperoxide generation promoted by the nanoparticles. Altogether, we report on novel ferroptosis-inducing iron encapsulated nanoparticles with potent anti-cancer properties, which has promising potential for further in vivo validation.